기상 합성 TiO2 나노입자의 특성 및 광촉매 특성 - 이명훈; 김민수; 진성민; 박은석; 이교우 (한국환경과학회, 2010)
The generation of TiO2 nanoparticles by a thermal decomposition of titanium tetraisopropoxide (TTIP) was carried out experimentally using a tubular electric furnace at various synthesis temperatures (700, 900, 1100 and 1300℃) and precursor heating temperatures (80, 95 and 110℃). Effects of degree of crystallinity, surface area and anatase mass fraction of those TiO2 nanoparticles on photocatalytic properties such as decomposition of methylene blue was investigated. Results show that the primary particle diameter obtained from thermal decomposition of TTIP was considerably smaller than the commercial photocatalyst (Degussa, P25). Also, those specific surface areas were more than 134.4㎡/g. Resultant TiO2 nanoparticles showed improved photocatalytic activity compared with Deggusa P25. This is contributed to the higher degree of crystallinity, surface area and anatase mass fraction of TiO2 nanoparticles compared with P25.